Relations of k-th derivative of dirac delta in hypercone with ultrahyperbolic operator - Aguirre T., Manuel A. (1999)
In this paper we prove that the generalized functions d (k) (P+) - d (k) (P), d (k) (P-)-d (k) (-P) and d 1 (k) (P)-d 2 (k) (P)d are concentrated in the vertex of the cone P=0 and we find their relationship with the ultrahyperbolic operator iterated (k +1 -n/2 ) times under condition k ³ n/2-1.